Cellular synthesis of protein pretzelanes. (June 2022) - Bai, Xilin; Liu, Yajie; Lee, Jiyeon; Fang, Jing; Wu, Wen-Hao; Seo, Jongcheol; Zhang, Wen-Bin
Abstract: Topology has been recognized as a unique dimension in molecular engineering, yet the topological diversity remains largely untapped, especially in macromolecules. Herein, we report the molecular design, cellular synthesis, and detailed characterization of protein pretzelanes with a chemical topology of a bridged Hopf link. The synergy between the intramolecular chain entwining guided by the p53dim (X) domains and the genetically encoded side-chain coupling by SpyTag(A)-SpyCatcher(B) reaction facilitates the direct synthesis of the model protein pretzelane BXA-BXA in Escherichia coli . The approach tolerates the insertion of various proteins-of-interest, such as elastin-like protein (ELP), superfolder green fluorescent protein (GFP) and dihydrofolate reductase (DHFR), at the bridge region between two rings, giving rise to three protein pretzelanes BXA-ELP-BXA, BXA-GFP-BXA, and BXA-DHFR-BXA. Their topology has been verified by combined techniques of MALDI-TOF mass spectrometry, ion mobility-mass spectrometry, site-specific mutation, and orthogonal proteolytic digestion experiments. Not only are the fluorescent properties of GFP and the catalytic properties of DHFR fully retained, the pretzelane topology also renders BXA-DHFR-BXA more thermally resilient than the wild-type DHFR. These results expand the topological diversity of proteins and demonstrate protein stabilization as a potential functional benefit for the pretzelane topology. Graphical abstract: Image, graphical abstract